2015
DOI: 10.1186/s12885-015-1100-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-4 is associated with tumor progression and a poor prognosis in ovarian carcinomas

Abstract: BackgroundFibulin-4, a member of the fibulin family of extracellular glycoproteins, is implicated in the progressions of some cancers. However, no information has been available to date regarding the function of fibulin-4 in ovarian carcinoma progression.MethodsIn this study, fibulin-4 mRNA and protein expression in normal ovarian tissue, ovarian tumor, high invasive subclones and low invasive subclones were evaluated by immunohistochemistry and real time reverse transcriptase-polymerase chain reaction (RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…18,27 EFEMP2 expression was up-regulated in cervical carcinoma and ovarian cancer, and its overexpression was significantly associated with the patient's adverse clinical and pathological characteristics and poor prognosis. 16,17 However, there were some opposite conclusions in the study of other tumors. EFEMP2 was weakly expressed in prostate carcinoma cell lines compared to normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,27 EFEMP2 expression was up-regulated in cervical carcinoma and ovarian cancer, and its overexpression was significantly associated with the patient's adverse clinical and pathological characteristics and poor prognosis. 16,17 However, there were some opposite conclusions in the study of other tumors. EFEMP2 was weakly expressed in prostate carcinoma cell lines compared to normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The role of EFEMP2 in tumorigenesis has not yet been fully elucidated, both carcinogenic and anti-carcinogenic effects have been reported. High expression of EFEMP2 was associated with tumor progress and poor prognosis in cervical carcinoma, 16 ovarian carcinoma, 17 glioblastoma 18 and osteosarcoma. 19 However, in human endometrial carcinoma, EFEMP2 demonstrated inhibitory effects in tumor invasion and metastasis.…”
Section: Introductionmentioning
confidence: 96%
“…FBLN4 promoter methylation has frequently been found in lung cancers43 and melanoma cells 44. Other studies have reported that FBLN4 is overexpressed in tumors of the digestive system4547 and in gynecological tumors;4850 FBLN4 overexpression correlates with tumor progression and poor prognosis in these studies. In contrast, FBLN4 is downregulated in prostate cancer 51.…”
Section: Discussionmentioning
confidence: 50%
“…Comparison of human colon tumors and adjacent normal tissue showed that tumors had a 2–7 fold increase at the EFEMP2 mRNA level 10. In cervical and ovarian carcinoma,11,12 EFEMP2 was overexpressed in cancer tissues and significantly related to poor clinicopathological characteristics. EFEMP2 expression was also found to be upregulated in osteosarcoma tissues and highly invasive cell lines, where EFEMP2 acted as a promoter for the development of osteosarcoma 13.…”
Section: Discussionmentioning
confidence: 96%